Electrooxidative Rhodium‐Catalyzed [5+2] Annulations via C−H/O−H Activations. Issue 12 (8th February 2021) - Wang, Yulei; Oliveira, João C. A.; Lin, Zhipeng; Ackermann, Lutz
Abstract: Electrooxidative annulations involving mild transition metal‐catalyzed C−H activation have emerged as a transformative strategy for the rapid construction of five‐ and six‐membered heterocycles. In contrast, we herein describe the first electrochemical metal‐catalyzed [5+2] cycloadditions to assemble valuable seven‐membered benzoxepine skeletons by C−H/O−H activation. The efficient alkyne annulation featured ample substrate scope, using electricity as the only oxidant. Mechanistic studies provided strong support for a rhodium(III/I) regime, involving a benzoxepine‐coordinated rhodium(I) sandwich complex as the catalyst resting state, which was re‐oxidized to rhodium(III) by anodic oxidation. Abstract : Electrochemical rhodium‐catalyzed [5+2] cycloadditions to assemble seven‐membered benzoxepines have been accomplished guided by detailed mechanistic insights.